ANALISIS PERANCANGAN SISTEM PENGGAJIAN TENTOR BIMBEL MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Widiyanti, Sri; Aziz, Riyan Abdul; Yustanti, Dyah Rosna (Universitas Budi Luhur, 2024)
Tutoring Salsabila (Tutoring) is a business that operates in the field of informal education. In this tutoring system, the attendance system and payroll for tutors is still done manually, namely in the attendance system the tutors come and then fill in the attendance list on the attendance sheet form that has been provided. The salary is calculated according to the number of attendance accumulated in one week. The problems that often occur in mentor payroll are that tutors forget the number of meetings because they forgot to fill in attendance, often experience errors because there are differences in attendance data between tutors and the admin section, and it takes a long time to process and search for the data. Method used to design this tutoring payroll system uses data collection consisting of observation, interviews and literature study. Then for analysis, use PIECES. Meanwhile, the system development method uses Rapid Application Development. In designing the system design, use case diagrams and prototype designs are used. This research focuses on the tutor payroll system and the aim of this research is to make it easier for admins to calculate salaries, find out payroll reports, and tutors can also get pay slips and payroll notifications. It is hoped that the results of this research can help tutors and using the payroll system, making it easier for tutors to input attendance and salary receipts, it is hoped that it will also make it easier for tutors to report, and in real time.